Non-effectiveness of Ivermectin on Inpatients and Outpatients With COVID-19; Results of Two Randomized, Double-Blinded, Placebo-Controlled Clinical Trials - Rezai, Mohammad Sadegh; Ahangarkani, Fatemeh; Hill, Andrew; Ellis, Leah; Mirchandani, Manya; Davoudi, Alireza; Eslami, Gohar; Roozbeh, Fatemeh; Babamahmoodi, Farhang; Rouhani, Nima; Alikhani, Ahmad; Najafi, Narges; et al. (Frontiers in Medicine, 2022)
Background Ivermectin which was widely considered as a potential treatment for COVID-19, showed uncertain clinical benefit in many clinical trials. Performing large-scale clinical trials to evaluate the effectiveness of this drug in the midst of the pandemic, while difficult, has been urgently needed. Methods We performed two large multicenter randomized, double-blind, placebo-controlled clinical trials evaluating the effectiveness of ivermectin in treating inpatients and outpatients with COVID-19 infection. The intervention group received ivermectin, 0.4mg/kg of body weight per day for 3 days. In the control group, placebo tablets were used for 3 days. Results Data for 609 inpatients and 549 outpatients were analyzed. In hospitalized patients, complete recovery was significantly higher in the ivermectin group (37%) compared to placebo group (28%; RR, 1.32 [95% CI, 1.04–1.66]; p-value = 0.02). On the other hand, the length of hospital stay was significantly longer in the ivermectin group with a mean of 7.98 ± 4.4 days compared to the placebo receiving group with a mean of 7.16 ± 3.2 days (RR, 0.80 [95% CI, 0.15–1.45]; p-value = 0.02). In outpatients, the mean duration of fever was significantly shorter (2.02 ± 0.11 days) in the ivermectin group versus (2.41 ± 0.13 days) placebo group with p value = 0.020. On the day seventh of treatment, fever (p-value = 0.040), cough (p-value = 0.019), and weakness (p-value = 0.002) were significantly higher in the placebo group compared to the ivermectin group. Among all outpatients, 7% in ivermectin group and 5% in placebo group needed to be hospitalized (RR, 1.36 [95% CI, 0.65–2.84]; p-value = 0.41). Also, the result of RT-PCR on day five after treatment was negative for 26% of patients in the ivermectin group versus 32% in the placebo group (RR, 0.81 [95% CI, 0.60–1.09]; p-value = 0.16). Conclusion Our data showed, ivermectin, compared with placebo, did not have a significant potential effect on clinical improvement, reduced admission in ICU, need for invasive ventilation, and death in hospitalized patients; likewise, no evidence was found to support the prescription of ivermectin on recovery, reduced hospitalization and increased negative RT-PCR assay for SARS-CoV-2 5 days after treatment in outpatients. Our findings do not support the use of ivermectin to treat mild to severe forms of COVID-19. Clinical Trial Registration www.irct.ir IRCT20111224008507N5 and IRCT20111224008507N4.